Anisotropic stimuli-responsive polymeric materials: chemistry and applications - Yuan Zhang; Yuan Zhang; Zhimin Lu; Changming Wu; Yang Xu (Frontiers in Materials)
Anisotropic stimuli-responsive polymeric materials (ASRPM) exhibit distinct physical and chemical properties along various orientations and can respond to external stimuli, demonstrating exceptional adaptability and functional integration capabilities. As research advances, new discoveries and applications continue to emerge, further enhancing the appeal of these materials. Despite an increase in related publications, there remains a relative scarcity of systematic summaries. In this mini-review, we summarize the research advancements in this field over the past decade, focusing on the structural properties, fabrication methods, advantages, and potential applications of ASRPM. We present a synthesized overview through illustrative charts, aiming to provide readers with a representative snapshot of the dynamic research landscape.